Embedded Micro-channel Cooling Technique to Minimize Thermal Deformation of X-ray and High-power Laser Optics. Issue 1 (1st December 2022) - Wei, Tiwei; Zhang, Lin; Asheghi, Mehdi; Goodson, Kenneth E.
Abstract: The thermal deformation of silicon-based X-ray and high-power laser optics is a strong function of the beam power and footprint, mirror geometry as well as the location of the "convective" thermal management solution. Previous research carefully optimized the impact of these parameters and arrived at the "Topside cooling" design concept (smart-cut notches) that reduced the thermal slope error (sub-μrads) by 3-5 orders of magnitude compared to the baseline mirror bottom-side cooling [1, 2]. The present work introduces internal embedded microchannel cooling which brings the cooling solution to the close proximity of the laser beam footprint and also reduce thermal spreading. The thermomechanical finite element modelling (FEM) results show that embedded microchannel cooling can reduce the thermal deformation in RMS- Uy by a factor of 40 and 13 compared with topside cooling, for Gaussian distribution beam heat flux with full width half maximum (FWHM) 20 mm and 40 mm, respectively.